Orientation relationship of eutectoid FeAl and FeAl2. Issue 2 (24th February 2016) - Scherf, A.; Kauffmann, A.; Kauffmann-Weiss, S.; Scherer, T.; Li, X.; Stein, F.; Heilmaier, M.
Abstract : The orientation relationship and interface plane of eutectoid FeAl and FeAl2 lamellae are investigated in detail and a crystallographic model is proposed. Abstract : Fe–Al alloys in the aluminium range of 55–65 at.% exhibit a lamellar microstructure of B2‐ordered FeAl and triclinic FeAl2, which is caused by a eutectoid decomposition of the high‐temperature Fe5 Al8 phase, the so‐called ϵ phase. The orientation relationship of FeAl and FeAl2 has previously been studied by Bastin et al. [ J. Cryst. Growth (1978), 43, 745] and Hirata et al. [ Philos. Mag. Lett. (2008), 88, 491]. Since both results are based on different crystallographic data regarding FeAl2, the data are re‐evaluated with respect to a recent re‐determination of the FeAl2 phase provided by Chumak et al. [ Acta Cryst. (2010), C66, i87]. It is found that both orientation relationships match subsequent to a rotation operation of 180° about a ⟨112⟩ crystallographic axis of FeAl or by applying the inversion symmetry of the FeAl2 crystal structure as suggested by the Chumak data set. Experimental evidence for the validity of the previously determined orientation relationships was found in as‐cast fully lamellar material (random texture) as well as directionally solidified material (∼⟨110⟩FeAl || solidification direction) by means of orientation imaging microscopy and global texture measurements. In addition, a preferential interface between FeAl and FeAl2 was identified by means of trace analyses using cross sectioning with a focused ion beam. On the basis of these habit planes the orientation relationship between the two phases can be described by ( 01)FeAl || (114) and [111]FeAl || [1 0] . There is no evidence for twinning within FeAl lamellae or alternating orientations of FeAl lamellae. Based on the determined orientation and interface data, an atomistic model of the structure relationship of Fe5 Al8, FeAl and FeAl2 in the vicinity of the eutectoid decomposition is derived. This model is analysed with respect to the strain which has to be accommodated at the interface of FeAl and FeAl2 .